Corticospinal Excitability of the Lower Limb Muscles During the Anticipatory Postural Adjustments: A TMS Study During Dart Throwing - Matsumoto, Amiri; Liang, Nan; Ueda, Hajime; Irie, Keisuke (Frontiers in Human Neuroscience, 2021)
Objective: To investigate whether the changes in the corticospinal excitability contribute to the anticipatory postural adjustments (APA) in the lower limb muscles when performing a ballistic upper limb movement of dart throwing. Methods: We examined the primary motor cortex (M1) excitability of the lower limb muscles (tibialis anterior and soleus muscles, TA and SOL) during APA phase by using transcranial magnetic stimulation (TMS) in healthy volunteers. Surface electromyography (EMG) of anterior deltoid, triceps brachii, biceps brachii, TA, and SOL muscles were recorded, and the motor evoked potential (MEP) to TMS were recorded in the TA muscle along with SOL muscle. TMS at the hotspot of TA muscle was applied at the timings immediately prior to the TA onset. The kinematic parameters including the three-dimensional motion analysis and center of pressure (COP) during dart throwing were also assessed. Results: The changes in COP and EMG of TA muscle occurred preceding the dart throwing which involved a slight elbow flexion followed by an extension. Correlation analysis revealed the onset of TA muscle was related to that of COP change as well as elbow joint flexion. The MEP amplitude in the TA muscle, but not that in the SOL muscle, significantly increased immediately prior to the EMG burst (100, 50 and 0 ms prior to the TA onset). Conclusion: Our findings demonstrate the corticospinal excitability of TA muscle increases prior to the ballistic upper limb movement of dart throwing, suggesting the corticospinal pathway contributes to the APA in the lower limb in a muscle-specific manner.